2009
DOI: 10.1038/nrg2681
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate limb bud development: moving towards integrative analysis of organogenesis

Abstract: The limb bud is of paradigmatic value to understanding vertebrate organogenesis. Recent genetic analysis in mice has revealed the existence of a largely self-regulatory limb bud signalling system that involves many of the pathways that are known to regulate morphogenesis. These findings contrast with the prevailing view that the main limb bud axes develop largely independently of one another. In this Review, we discuss models of limb development and attempt to integrate the current knowledge of the signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
417
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(440 citation statements)
references
References 106 publications
7
417
1
7
Order By: Relevance
“…At precondensation stages, distal limb bud mesenchyme expresses both Fgfr1 and Fgfr2 (Orr-Urtreger et al 1991;Sheeba et al 2010), whereas Fgfr3 and Fgfr4 are not detected in undifferentiated distal limb bud mesenchyme (Sheeba et al 2010). Distal limb bud FGFRs respond to FGFs produced by the apical ectodermal ridge (AER) of the limb bud (Zeller et al 2009). AER FGFs (primarily FGF4 and FGF8) signal to limb mesenchyme and are required for proximo-distal outgrowth of the limb bud.…”
Section: Fgf Signaling During Skeletal Developmentmentioning
confidence: 99%
“…At precondensation stages, distal limb bud mesenchyme expresses both Fgfr1 and Fgfr2 (Orr-Urtreger et al 1991;Sheeba et al 2010), whereas Fgfr3 and Fgfr4 are not detected in undifferentiated distal limb bud mesenchyme (Sheeba et al 2010). Distal limb bud FGFRs respond to FGFs produced by the apical ectodermal ridge (AER) of the limb bud (Zeller et al 2009). AER FGFs (primarily FGF4 and FGF8) signal to limb mesenchyme and are required for proximo-distal outgrowth of the limb bud.…”
Section: Fgf Signaling During Skeletal Developmentmentioning
confidence: 99%
“…Together, the AER and ZPA coordinate gradients of growth factors to regulate formation, size, shape, and location of future bone and joints in the appendicular skeleton (reviewed in Johnson and Tabin 1997;Galloway and Tabin 2008). Interlinked feedback loops between AER, ZPA, and mesenchymal BMP signaling regulate initiation, propagation, and termination of the limb signaling system (reviewed in Benazet et al 2009;Zeller et al 2009). Disruption of these feedback loops result in impaired progression of limb bud development and specification of digit identity (Kawakami et al 1996;Ahn et al 2001;Khokha et al 2003;Ovchinnikov et al 2006;Montero et al 2008;Suzuki et al 2008;Benazet et al 2009).…”
Section: Roles Of Tgf-b and Bmp Signaling In Limb Formation And Digitmentioning
confidence: 99%
“…These CNEs participate in gene regulatory networks for axial formation, outgrowth, and chondrogenic differentiation in limb development (Zeller et al 2009). We found apparent sequence similarity in CNEs for the limb enhancer of bmp7 (Adams et al 2007) and the limb enhancer (CNE11) of gli3 (Abbasi et al 2010) between tetrapods and coelacanth, whereas such similarities were not observed in the corresponding genomic regions of ray-finned fishes (Fig.…”
Section: Genes For Limb Developmentmentioning
confidence: 99%